CHANGE AND CONTINUITY IN INDONESIAN FOREIGN POLICY - Yanyan Mochamad Yani (Universitas Padjadjaran, 2009)
This article focuses on Indonesian foreign policy change and continuity and then the discussion of foreign policy at present. The analysis is carried out in six periods of Indonesia’s foreign policy change and continuity, namely Soekarno’s Old Order Era period (1945-1965), Soeharto’s New Order Era period (1965-1998), and four Indonesian governments in the Reformation Era; Habibie period (1998-Oct1999), Abdurahman Wahid period (1999-July 2001), Megawati Soekarnoputri period (2001-October 2004), and Susilo Bambang Yudhoyono period (2004 – now). This paper concludes that since the fall of Soeharto, Indonesia’s diplomacy was called upon to play a substantive role in meeting an array of challenges in the economic, political and social fields that threatened the unity, integrity, and sovereignty of the Republic.